'I like the idea but…': the gap in participation in a virtual community of practice for analysing physical education. (2nd September 2019) - García-Monge, Alfonso; González-Calvo, Gustavo; Bores-García, Daniel
ABSTRACT: The dynamics of a community of practice are full of tensions and changes regarding possibilities and types of participation. The case study in this paper followed the approach of Stake by focusing on the tension between the willingness to participate and actual participation in an online social network called MultiScopic which involves children of a primary school, their families and in-service physical education teachers, as well as teacher-training students and their professors. Fifty-six participants were invited to take part in MultiScopic over three years, and data was collected through different qualitative procedures. Initially, all participants foresaw a great potential for this kind of virtual community of practice. Later, participation would drop off for reasons such as laziness and lack of time, caution when posting texts to an online site, fear of being judged and inhibition when other, more academically advanced participants engaged in commentary. Participants stated that MultiScopic helped them to feel professionally active, to appreciate the richness of their profession and to discover occupational possibilities.